Preparation and characterization of membranes supports for filtration application. (2022) - Harinkhere, Disha; Kaurav, Netram; Okram, G.S.
Highlights: The membrane supports prepared by wet pressing method. XRD confirms the formation of nanocrystalline powders. Average pore size of the membrane supports is increased by increasing temperature. TGA analysis indicated the sample loses around 2.4 wt%. Abstract: The current research is focused on preparation of robust filtration membrane support. Present work reported the fabrication of membrane supports based on alumina and calcium carbonate. By applying a uniaxial compression pressure of 2.5 tons per inch to final powder, disc-shaped membrane supports were produced. Further, the discs supports were heated at varied sintering temperatures of 1100 °C, 1200 °C, and 1300 °C for 5 h to evaluate the influence of different sintering temperatures on membrane support characteristics. To study the effect of maximum sintering temperature on prepared membrane support structure and porosity, the membrane supports were cast as circular discs with diameter of 23 mm and thickness of 2 mm. Prepared membrane supports were characterized using XRD, FESEM, and TGA analyses. XRD results reveal the formation of nanocrystalline powders before palletisation. FESEM images analysis revealed the average pore size of the membrane supports was increase from 5 nm to 14 nm when sintering temperature increased from 1100 °C to 1300 °C. TGA analysis showed that the sample loses about 2.4 wt% between 32 and 900 °C, while DTA curves exhibited two substantial endothermic peaks at 323.4 °C and 526.8 °C.